British and French Colonialism in Africa, Asia and the Middle East: Connected Empires across the Eighteenth to the Twentieth Centuries - Fichter, James R. (Cambridge Imperial and Post-Colonial Studies Series, 2019)
Chapter 1. Introduction. Britain and France, Connected Empires -- Part I: Empire in Africa -- Chapter 2. “From Slaves to Gum: Colonial Trade and French-British Rivalry in Eighteenth-Century Senegambia.” Cheikh Sène -- Chapter 3. “'Our Anglo-Saxon Colleagues:' The Constraining Embrace of British Northern Nigeria." Barbara Cooper -- Part II: Empire and Islam -- Chapter 4. “Anglo-French Connections and Cooperation against ‘Islamic’ Resistance, 1914-1917” John Slight -- Chapter 5. “Sacred Surveillance: Indian Muslims, Syrian Waqf, and the Evolution of State Surveillance in Syria under the French Mandate.” James Casey -- Part III: Empire at Sea -- Chapter 6. “A Shared Sea: The Axes of French and British Imperialism in the Mediterranean, 1798-1914” -- Chapter 7. “A Second ‘Fashoda?’: Britain, India and a French ‘Threat’ in Oman at the End of the Nineteenth Century” Guillemette Crouzet -- Chapter 8. “Imperial Interdependence on Indochina's Maritime Periphery: France and Coal in Ceylon, Singapore and Hong Kong, 1859-1895” James R. Fichter -- Chapter 9. “French Kwang-Chow-Wan and British Hong Kong: Politics and Shipping, 1890s-1920s” Bert Becker -- Part IV: Empire and Administration -- Chapter 10. “Sharing Colonial Sovereignty? The Anglo-French Experience of the New Hebrides Condominium, 1880s-1930s” Hélène Blais -- Chapter 11. “British and French Colonial Statistics: Development by Hybridization from the Eighteenth to the mid-20th Centuries” Béatrice Touchelay -- Part V: Imperial Ends -- Chapter 12. “Britain and Free France in Africa, 1940-1943” -- Chapter 13. “The End of Empires and Some Linguistic Turns: British and French Language Policies in Inter- and Post-War Africa” Diana Lemberg